Answer:
x = ±2
Step-by-step explanation:
A equation is given to us , which is ,

From <u>properties </u><u>of </u><u>logarithm </u>we know that ,

Applying this to LHS , we have ;

Now the bases of logarithm on LHS and RHS is same . On comparing , we have ;

Put square root on both sides,

Simplify ,

This is the required answer.
Is that supposed to be x squared, or x times 2 in the beginning of the first one?
Answer: c. f - 3 + 6d
Explanation: 5d - d + 4 + 2d - 5f - 6f - 7
- 5f - 6f = f
4 - 7 = -3
5d - d = 4d, 4d + 2d = 6d
Answer:
y = 394
Step-by-step explanation: